The Picasso heist [large type] - Patterson, James, 1947-; Roughan, Howard (Little, Brown and Company, 2025)
"The art world ignites with the discovery of a previously unknownPicasso painting. After being hidden away for fifty years in the attic of a French villa, it's valued at $100 million and put up for auction. Echelon, the Upper East Side auction house brokering the sale, is flooded with interest. ... None of the interested parties has a chance at winning the Picasso without the help of Halston Graham. The young auction-house employee graduated second in her class at Columbia, but she's a first-rate art thief--and an expert gambler who knows how to calculate the odds and play her considerable leverage against all sides. To complete the Picasso heist, she must stay one step ahead of the truth before the gavel falls"--